Activity and microbiological monitoring of Ismett's galenic laboratory. Issue 2 (12th March 2012) - Bavetta, S.; Casucci, I.; Di Stefano, R.; Polidori, P.
Abstract : Background: Intravenous sterile galenic preparations allow unit dose personalised therapy for patients. The assurance of sterile preparations, especially in a transplant centre that treats immunocompromised patients, must be guaranteed by dedicated rooms and equipment, qualified personnel and application of aseptic techniques. Purpose: The goal of the study is to evaluate the activity and safety of the pharmacy compounding laboratory. Materials and methods: Ismett hospital has about 90 beds and an average of 2000 patients / year. Compounds sterile medications in a laminar flow hood in our class 10, 000 clean room guarantee safety and quality products by following Italian rules of good manufacturing (NBP), Good Manufacturing Practice (GMP) and microbiological testing incorporate on a regular basis. Intravenous galenic preparations were monthly tested for determination of aerobic / anaerobic bacteria and bacterial endotoxins by Lymulus Amebocyte Lysate test. Environmental, surface and personnel were tested every three months. Results: 75, 000 intravenous preparations were performed from January to September 2011, with an average of 8322 monthly and 275 daily doses. 31% continuous infusions and 69% bolus, (46% antibiotics, 12% gastroprotectors, 9% cardiac stimulants, 5% antihypertensives, 1.5??% antiarrhythmics, 7% hypoglycaemics, 6% anaesthetics, 5% antithrombotics, 2% antifungals, 1% antivirals, 8.5% others). Environmental samples, personnel hands and galenic preparations were always negative (100%). 25% of the surface samples were positive for coagulase-negative staphylococci, oryzihabitan Pseudomonas, Sphingomonas paucimobilis, Sphingomonas spp and Acinetobacter spp, micrococci and Alternaria fungi. Consequently some strictly corrective measures have been adopted to avoid positive surface samples. Conclusions: Considering the large number of daily preparations, periodical microbiological monitoring is essential to take the necessary corrective measures to reduce microbial load and ensure the quality and sterility of preparations.